PENGARUH ASAP ROKOK TERHADAP PERUBAHAN WARNA PADA BASIS GIGI TIRUAN RESIN TERMOPLASTIK NILON (Penelitian pada 2 Jenis resin termoplastik nilon berdasarkan suhu pembuatan 287,7Â° C dan 302Â° C) - Rahmah, Riezki Amalia; Saputera, Debby; Puspitasari, Dewi (Dentino, 2017)
ABSTRACTBackground:Loss of teeth could impact on the mastication efficiency. To overcome this problem, the patient can wore denture or prosthesis. One of thematerials to made denture base is ValplastÂ® and LucitoneÂ® FRSâ¢. Denture base material was likely to absorbed various of contaminants such as tar that were contained in cigarettes. It became a factor of discoloration on denture base. Purpose: To determine whether there was a color change of the nylon thermoplastic resin after exposed to cigarette smoke. Methods:This type of research was true experimental with post-test only and control design, the number of samples that used were 24 pieces consisting of four groups, two of them were ValplastÂ®, one group exposed to smoke and others were not exposed to smoke and the other two groups were LucitoneÂ® FRSâ¢, one group were exposed to smoke and others were not exposed to smoke. Result:There were significant differences between the group of ValplastÂ® that exposed to smoke with the group of ValplastÂ® that not exposed to smoke of 0.000 (p<0.05) and between the group of LucitoneÂ® FRSâ¢ that exposed to smoke with the group of LucitoneÂ® FRSâ¢ that not exposed to smoke of 0.000 (p<0.05) as well as between the group of ValplastÂ® that exposed to smoke with the group of LucitoneÂ® FRSâ¢ that exposed to smoke of 0.000 (p<0.05).Conclusion: There were changed of color in the nylon thermoplastic resin after exposed to cigarette smoke.Keywords: Nylon thermoplastic resin, Discoloration, Cigarette smoke.